2012
DOI: 10.1155/2012/387971
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Thyroid Volume by Ultrasonography among Schoolchildren in Philippines

Abstract: Objective. Iodine deficiency is defined by the goiter and the urinary iodine concentration. However, a lack of local thyroid volume reference data resulted in the vague definition of goiter, especially in school-aged children. The aim of this paper was to determine the thyroid volumes by ultrasonography in schoolchildren aged 6 to 12 years living in Cagayan areas in Philippine. Methods. Cross-sectional thyroid ultrasonographic data of 158 schoolchildren aged 6–12 years from Tuguegarao and Lagum in Cagayan vall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 20 publications
2
19
2
1
Order By: Relevance
“…MUIs in our samples indicated iodine sufficiency, so genetic features in growth and development may have mainly contributed to the influence on thyroid volume. In our study, as in others [30, 31, 35, 36, 39], BSA and age, independently of each other, significantly positively influenced thyroid volume; these parameters are used to assess thyroid volume as adjusted predictors. However, regarding the correlation between thyroid volume and sex, UICs were not obtained, and these findings were in line with the results reported in most iodine-sufficient areas [10, 36, 37].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…MUIs in our samples indicated iodine sufficiency, so genetic features in growth and development may have mainly contributed to the influence on thyroid volume. In our study, as in others [30, 31, 35, 36, 39], BSA and age, independently of each other, significantly positively influenced thyroid volume; these parameters are used to assess thyroid volume as adjusted predictors. However, regarding the correlation between thyroid volume and sex, UICs were not obtained, and these findings were in line with the results reported in most iodine-sufficient areas [10, 36, 37].…”
Section: Discussionsupporting
confidence: 67%
“…In this study, the MUI in the study's schoolchildren was 178.30  μ g l −1 , which was similar to the data reported in Germany (183.00  μ g l −1 ) [28] and Bahrain (178.00  μ g l −1 ) [13] but higher than that in Turkey (53.00  μ g l −1 ) [29], Bangladesh (73  μ g l −1 ) [10], Switzerland (115 and 118.00  μ g l −1 ) [11, 13], Sweden (125.00  μ g l −1 ) [30], Italy (125.00  μ g l −1 ) [31], Malaysia (132.80  μ g l −1 ) [9], Netherlands (154.40  μ g l −1 ) [32], and Poland (126.60–155.10  μ g l −1 ) [33] and less than that in South Africa (191.00  μ g l −1 ) [13], Iran (212.00  μ g l −1 ) [34], Peru (253.00  μ g l −1 ) [13], Philippines (279.00  μ g l −1 ) [35], the United States (282.00 and 285.00  μ g l −1 ) [10, 13], Japan (281.60 and 288  μ g l −1 ) [13, 36], and Brazil (360.00  μ g l −1 ) [37]. Compliance with the Universal Salt Iodization program has been mandatory since 1994 in Zhejiang Province, China, which was identified as iodine sufficient for decades in several sustained surveys from 1995 to 2011 [38].…”
Section: Discussionmentioning
confidence: 99%
“…Among 6 regions in the world, children in Japan, as representatives of the Asian region, had both the largest age-adjusted thyroid volumes and the largest body surface area-adjusted thyroid volumes. After publishing these data, recent studies on thyroid volume confirmed the international reference values although the number of cases are small (approximately 200-5000 cases) in all studies [11][12][13][14][15][16]. In Japan, Fuse et al compared the international reference values for Japanese and thyroid volumes of approximately 1000 schoolchildren [11].…”
Section: Discussionmentioning
confidence: 93%
“…The thyroid gland increases in size as children grow, and some studies have suggested that there is no significant difference in thyroid volume between genders, and others stated that differences were seen post‐puberty . Age, sex and anthropometric characteristics such as body surface area (BSA), weight and height of individuals are positively associated with thyroid volume . Thyroid volume as a function of BSA takes into account the difference in body development between children of the same age especially in developing countries .…”
Section: Anthropometric Characteristicsmentioning
confidence: 99%